2021
DOI: 10.1080/20020317.2021.1980275
|View full text |Cite
|
Sign up to set email alerts
|

Saving racialized children through good schooling: media discourses on racialized children’s schooling as a site for upholding danish whiteness

Abstract: This article uses Danish media discourses on racialized children's schooling as a lens through which to analyse how issues of kinship and family play into nation-building processes through representations of 'the child'. The article addresses the question of the distribution of racialized children, mostly termed 'bilingual pupils', at Danish schools, which is a recurrent theme in the public debate. The media representation of this issue is mostly framed around an ideal of spreading the 'bilingual pupils' among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…However, as Faulkner (2010) notes: 'Despite our love for children, then, the importance of innocence has little to do with their welfare, and a great deal to do with adults' discomfort in the world' (p. 18). For instance, the discomfort when being confronted with one's own privileges and responsibilities relating to the still-existing racialized social structures and hierarchies (see Wekker, 2016;Ahmed, 2013), ultimately challenging a self-image of being 'good' (Smedegaard Nielsen, 2021;Sue, 2010).…”
Section: Staying With the Discomfort Of/and Not Claiming White Innocencementioning
confidence: 99%
See 1 more Smart Citation
“…However, as Faulkner (2010) notes: 'Despite our love for children, then, the importance of innocence has little to do with their welfare, and a great deal to do with adults' discomfort in the world' (p. 18). For instance, the discomfort when being confronted with one's own privileges and responsibilities relating to the still-existing racialized social structures and hierarchies (see Wekker, 2016;Ahmed, 2013), ultimately challenging a self-image of being 'good' (Smedegaard Nielsen, 2021;Sue, 2010).…”
Section: Staying With the Discomfort Of/and Not Claiming White Innocencementioning
confidence: 99%
“…While this is a symptomatic example of Scandinavian silencing of racial injustice, it also shows how some children are perceived as more ‘desirable’, ‘welcomed’ and more in need of protection than their racially minoritized peers. Similarly, studies have suggested how ideas of belonging to the child or student category operate through intersecting processes of gender (Gilliam, 2018; Kofoed, 2008; Lagermann, 2014; Staunæs, 2004), religion (Khawaja, 2010; Buchardt, 2014) and race (Smedegaard Nielsen, 2021; Smedegaard Nielsen & Myong, 2019; Vertelytė, 2019) that work against minoritized children.…”
Section: Innocence In a Nordic Contextmentioning
confidence: 99%